2004
DOI: 10.1086/502328
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Transmission and antibiotic Adverse Events Among Neonates and Adults Exposed to a Healthcare Worker With Pertussis

Abstract: Although it was not possible to assess the effectiveness of the antibiotic regimens, the lack of laboratory-confirmed secondary cases suggests control measures were successful. Data from the 58 neonates who received azithromycin suggest it may be well tolerated in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…One particular study, which provided 1 of the largest cohorts of young infants observed for side effects of azithromycin, involved 58 neonates from the nursery who received a 5-day course of azithromycin after potential exposure to a rotating medical student with confirmed pertussis. 13 The antibiotic was well tolerated, and none of these infants (mean age of 15 days; range, 3-24 days) subsequently developed IHPS. However, 58 infants might have been too small a number to detect a possible underlying association with IHPS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One particular study, which provided 1 of the largest cohorts of young infants observed for side effects of azithromycin, involved 58 neonates from the nursery who received a 5-day course of azithromycin after potential exposure to a rotating medical student with confirmed pertussis. 13 The antibiotic was well tolerated, and none of these infants (mean age of 15 days; range, 3-24 days) subsequently developed IHPS. However, 58 infants might have been too small a number to detect a possible underlying association with IHPS.…”
Section: Discussionmentioning
confidence: 89%
“…The median (IQR) age for infants prescribed erythromycin and azithromycin was 49 days (23-70) and 68 days (50-80; P , .001), respectively. The median number of days after exposure to erythromycin in which the 17 infants underwent pyloromyotomy was 13 days (range, 2-40; IQR, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The median number of days between exposure to azithromycin in the 8 infants and subsequent pyloromyotomy was longer than the interval for the erythromycin group at 29.5 days (range, 9-45; IQR 20.5-38.5; P = .08).…”
Section: Resultsmentioning
confidence: 99%
“…The index case may be a patient (30,49), a health care worker (7,22,24,44,50,80), or a visitor (79,85). Subsequent exposures may result in transmission to a large number of health care workers and patients (22,48).…”
Section: Impact Of Pertussis In Health Care Settingsmentioning
confidence: 99%
“…Only a small number of infants treated with azithromycin after the first 6 weeks of life were included in the study by Mahon et al 3 None of them developed pyloric stenosis. In another study, 14 primarily designed to look at efficacy of azithromycin as a post-pertusis exposure chemoprophylactic agent, 58 neonates were given azithromycin. None of them developed pyloric stenosis.…”
Section: Commentsmentioning
confidence: 99%